One-pot formation of ultra-thin Ni/Co hydroxides with a sheet-like structure for enhanced asymmetric supercapacitors. Issue 23 (26th May 2016) - Ye, Lin; Zhao, Lijun; Zhang, Hang; Zhang, Bo; Wang, Huiyuan
Abstract : Ragone plot of the Ni/Co hydroxides (Ni1Co2)//AC device. Abstract : In our work, ultra-thin Ni/Co hydroxides (Ni1Co2) with a sheet-like structure are successfully grown on the surface of conductive nickel foam via a one-pot hydrothermal reaction, avoiding the need for binders and conducting agents. In the reaction, NO3 − ions from reactants release OH − ions partially with Co 2+ ions turning into Co 3+ ions and then OH − ions can react with Ni 2+, Co 2+ or Co 3+ in a mixed solvent of water and ethanol, without the necessary addition of an extra alkali source. When used for supercapacitors, the resulting free-standing Ni1Co2 composites exhibit an impressive specific capacitance of 2654.9 F g −1 at a current density of 1 A g −1 and a favorable cycling stability with 77% retention even at a high current density of 10 A g −1 after 1500 cycles. In order to do research into the electrochemical properties of Ni1Co2 composites, a simple asymmetric supercapacitor (ASC) is constructed, using the Ni1Co2 nanosheets as the positive electrode and activated carbon (AC) as the negative electrode. This ASC with an extended voltage window of 0–1.6 V presents an outstanding energy density of 42.4 W h kg −1 (at a power density of 823.2 W kg −1 ) and still retains 24.8 W h kg −1 (at 10 170.8 W kg −1 ). Meanwhile, the excellent cycling stability of this ASC device has been revealed via a great specific capacitance retention of 94% after 3000 cycles (at a current density of 5 A g −1 ). So the Ni1Co2-based composites could be one of the potential materials for high-performance energy storage.